Strategi Kreatif Pesan Iklan Ladang Coffee Dalam Membangun Brand Image Sebagai CoffeeShop Khas Nusantara - Iin Soraya (Universitas Bina Sarana Informatika, 2018)
Coffee activity is now a part of lifestyle, it is seen with the many emergence of coffee shop in Indonesia. Coffee shop offers a lot of coffee mix and modern concept, but Indonesia is one of the largest coffee producing countries. One of them is Coffee Field which gives different concept from other coffee shop that presents original Indonesian coffee with nuance nuance. But to win the Coffee Farm competition requires promotion through print ads in order to win the hearts of coffee consumers in Indonesia. The research used qualitative research approach, research type of descriptive qualitative analysis, by trying to interpret different research data. The object of this research is print advertisement of Rencong Coffee Field. Creative advertising advertising strategy print print Rencong Coffee Field is by using the big idea archipelago with the intention to highlight coffee and coffee shop typical of the archipelago is a coffee that comes from Indonesia and Coffee shop with the nuances of Indonesian culture. The type of attraction the message uses emotional appeal, because it does not directly display the product just the impression that represents the product. Strategy style of delivery of advertising messages Coffee Field is using the mood or image that evokes the atmosphere of the archipelago around the product. Keywords: Advertising Creative Strategy, Brand Image, Qualitative Descriptive Analysis